Building Resilience among Children and Youth with ADHD through Identifying and Developing Protective Factors in Academic, Interpersonal and Cognitive Domains - Genevieve Mackenzie (Journal of ADHD And Care, 2018)
Children and youth with ADHD are a vulnerable group susceptible to adversity in wide-ranging life domains. However, many children and youth, irrespective of having ADHD become successful both academically andinterpersonally, and improve their cognition. This group can be considered as being “resilient”, that is, adapting to the adversity they may face in a positive manner. The overarching goal of this paper is to highlight domains at the academic, interpersonal and cognition levels that are indicative of resiliency among children and youth with ADHD. The secondary goal is to highlight interventions that result in promoting resiliency among this group at these levels. It is necessary for future interventions to be designed and implemented with developing the resiliency of children and youth with ADHD in mind. To achieve this, research needs to begin to identify the strengths of children and youth with ADHD to provide insight into how their strengths can compensate for their weaknesses, and to promote their resiliency leading to success academically, interpersonally and cognitively.
Keywords: ADHD